Pencegahan Depresi Di Kalangan Dewasa Muda Akibat Pandemi Covid-19 Melalui Kampanye Sosial Pada Instagram - Amalia, Annisa; Anggraeni, Niken Savitri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The Covid-19 pandemic has caused various symptons of depression of the community from mild to severe levels. This is due to the fear of contracting the virus, the high death rate in Indonesia, economic problems, to confusing information on social media, one is young adults. One of the sufferers of depression is young adults. To prevent depression, a social campaign through digital media is needed to make it easily accessible to this young adults on of which is Instagram. Content with messages and illustrations is expected to be able to help young adults in preventing depression. This study aims to determine the design concept and design execution that appeals to young adults. The method used is qualitative method with a psychological and design approach to be able to formulate an interesting content through Instagram.